COMPETITIVE STRATEGY MODEL FOR PURBALINGGA BATIK - Suliyanto Suliyanto; Siti Zulaikha Wulandari; Weni Novandari (Economic Journal of Emerging Markets, 2010)
Batik Purbalingga has a promising role to increase society’s welfare in Purbalingga. This studyaims at investigating the problems of and formulating a competitive strategy for Purbalingga Batik,using an Analytical Hierarchy Process. It uses Strength, Weaknesses, Opportunities and Threatsand Quantitative Strategic Planning Matrix to formulate a competitive strategy for Purbalingga Batik.It finds that the operational factor, human resources, marketing, financial and business environmentare constraints to the formulating process, with operational factor as the dominant one. Itsuggests that the Strength-Opportunity is the appropriate tool to develop a competitive strategy forPurbalingga Batik.Keywords: Competitive strategy, analytical hierarchy process, quantitative strategic planning matrix,purbalingga batikJEL classification numbers: D21, D22